Construction of the Women's Discourse in the 2024 Elections on the Alternative Media Magdalene.co and Konde.co - Hikma, Izza Nadia; Tiani, Riris (Proceedings International Conference of Culture and Sustainable Development; Vol 2 (2024): PROCEEDINGS ICOCAS, 2024)
The 2024 election is an important moment for women's participation in Indonesia. Magdalene.co and Konde.co as alternative media play an important role in shaping the discourse around women and politics. This research aims to analyze how the two online media construct or shape the discourse of women in the 2024 elections. Furthermore, this research seeks to reveal the position of women politicians in the alternative media Magdalene.co and Konde.co. Using a qualitative methodology, this study focuses on a descriptive analysis of the news article texts from Magdalene.co and Konde.co. The research data taken are words, phrases, or sentences in the news discourse of the two alternative media that support research problems. The data analysis technique uses Sara Mills' theory of critical discourse analysis. The results show that Magdalene.co and Konde.co actively voice disapproval of gender discrimination and break down societal stereotypes by promoting gender equality for men and women. Magdalene.co tends to focus on empowering women and encouraging women's political participation. Meanwhile, Konde.co is more critical of gender issues in politics and gives voice to marginalized women. This research contributes to understanding how alternative media influences public opinion and shapes the narrative of women's participation in the 2024 election.
Keywords: alternative media, media construction, women politicians, election 2024, Sara Mills